PENINGKATAN KEMAMPUAN SISWA DALAM MENERAPKAN UNGGAH-UNGGUH BAHASA JAWA DENGAN TEKNIK BERMAIN PERAN (PLAY ROLE): SMPN 3 Pule Kabupaten Trenggalek - HARIADI HARIADI (Dewan Pendidikan Bondowoso, 2021)
The use of the Javanese language among students at this time is not paying attention to uploading. They talk to their peers and to those who are older in age, they do not differentiate, namely the use of the ngoko variety. Several things are the cause of the decline in students' Javanese speaking abilities, among others; (1) the influence of modernization; (2) demands for the use of national and international languages; (3) the social environment of students both in the family, school, and community is less supportive; (4) language learning in schools that have not been maximized. Various efforts have been made to improve students' Javanese language skills, especially in learning Javanese in class 9A of SMPN 3 Pule, Trenggalek Regency. one of them is to improve students' Javanese language skills through the role play method. Based on the results of the research and discussion, it can be concluded that: (1) students are very enthusiastic about learning by playing a role (2) students' ability to apply upload-ungguh Javanese language with role playing techniques increases.